Outcomes of pulmonary valve replacement using a bioprosthetic valve and polytetrafluoroethylene bicuspid valve for pulmonary valve regurgitation after intracardiac repair of tetralogy of Fallot. Issue 11 (22nd August 2021) - Akiyama, Sho; Kimura, Naritaka; Yamazaki, Masataka; Ito, Tsutomu; Shimizu, Hideyuki
Abstract: Background: Excellent results have been reported regarding pulmonary valve replacement (PVR) for pulmonary valve regurgitation (PR) after intracardiac repair (ICR) in patients with tetralogy of Fallot (TOF). However, there are apparently no reports comparing the following procedures: PVR using a bioprosthetic valve and PVR using a polytetrafluoroethylene (PTFE) bicuspid valve. Herein, we retrospectively analyzed the outcomes of PVR for PR after ICR of TOF in our institution and assessed which of the two PVR procedures was better. Methods: From June 2008 to December 2017, we performed PVR for PR after ICR of TOF in 34 patients. Patients with the right ventricle to the pulmonary artery conduits were excluded. Preoperative and postoperative cardiac magnetic resonance imagings (cMRIs) were performed in all patients. The patients were divided into the bioprosthetic valve group (BV group, n = 17) and the PTFE bicuspid valve group (PTFE group, n = 17). Results: There were no significant differences in the preoperative cMRI data and perioperative factors between the two groups. There were no deaths in either group. Postoperative cMRI showed that the PR fraction and the right ventricular end‐diastolic volume index (RVEDVI)/left ventricular end‐diastolic volume index ratio were significantly improved in both groups. However, RVEDVI was significantly improved only in the BV group. Re‐PVR was required in four patients in the PTFE group. Conclusion: PVR using a bioprosthetic valve was more effective for PR treatment after ICR of TOF than PVR using a PTFE bicuspid valve.